2015
DOI: 10.1086/681526
|View full text |Cite
|
Sign up to set email alerts
|

A life-history account ofMacrobrachium spinipes(Schenkel, 1902) (Cherabin) in a large tropical Australian River

Abstract: Rivers in tropical Australia are largely pristine, and ecosystem connectivity is intact, but water resources in northern Australia are under increasing development pressure. A better understanding of the role and life histories of key migratory species is urgently needed to manage the risks posed by development. We investigated the life history of Macrobrachium spinipes (Schenkel, 1902) in the Daly River of the Northern Territory, Australia. We carried out a 13-mo trapping program (2011-2012) at 7 sites along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…Our data suggested that selective tidal stream transport may play a role, however, more work on this aspect is required. This study builds upon the previous findings on the life history of M. spinipes (Novak et al, 2015(Novak et al, , 2016 and by doing so provides significant insights into the life history and flow ecology of an amphidromous shrimp inhabiting large low land river systems. This is key information for the management of these species should these river systems be impacted by future water resource developments.…”
Section: Biomass Estimation and Marine-freshwater Subsidiesmentioning
confidence: 60%
See 3 more Smart Citations
“…Our data suggested that selective tidal stream transport may play a role, however, more work on this aspect is required. This study builds upon the previous findings on the life history of M. spinipes (Novak et al, 2015(Novak et al, , 2016 and by doing so provides significant insights into the life history and flow ecology of an amphidromous shrimp inhabiting large low land river systems. This is key information for the management of these species should these river systems be impacted by future water resource developments.…”
Section: Biomass Estimation and Marine-freshwater Subsidiesmentioning
confidence: 60%
“…Novak et al. () also found that recruitment of juveniles was unidirectional, from the estuary to the fresh water, and that this recruitment occurred at the end of the wet season and early dry season. The main aim of the present study was to determine the phenology, magnitude and potential marine subsidy of an amphidromous shrimp migration in a large lowland river system.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Many species of freshwater decapods and some fish species present this type of adaptation (McDowall 2007). In this issue, Novak et al (2015) discuss the life history of a shrimp species from a large tropical river in Australia that follows this pattern. In addition, Crook et al (2015) discuss how the study of otolith microchemistry can aid in understanding the life histories of fish species that inhabit coastal rivers.…”
Section: Complex Life Historiesmentioning
confidence: 99%